A computational comparative analysis of the binding mechanism of molnupiravir's active metabolite to RNA‐dependent RNA polymerase of wild‐type and Delta subvariant AY.4 of SARS‐CoV‐2. Issue 4 (7th February 2022) - Celik, Ismail; Tallei, Trina E.
Abstract: The antiviral drug molnupiravir targets the SARS‐CoV‐2 RNA‐dependent RNA polymerase (RdRP) enzyme. Early treatment with molnupiravir reduced the risk of hospitalization or death in at‐risk, unvaccinated adults with COVID‐19, according to phase 3 clinical trials. Many mutations have occurred within this virus as a result of its widespread distribution. The current study sought to determine whether mutations in the RdRP of Delta subvariant AY.4 (D‐AY.4 RdRP) influence the interaction of the enzyme with molnupiravir triphosphate (MTP), the active metabolite of molnupiravir. The interactions between the wild‐type (WT) RdRP and D‐AY.4 RdRP with MTP were evaluated based on molecular docking and dynamic simulation (MD) studies. The results show that the MTP interaction is stronger and more stable with D‐AY.4 RdRP than with WT RdRP. This study provides insight into the potential significance of administering MTP to patients infected with D‐AY.4 RdRP, which may have a more favorable chance of alleviating the illness. According to the findings of this study, MTP has a high likelihood of becoming widely used as an anti‐SARS‐CoV‐2 agent. The fact that MTP is not only cytotoxic but also mutagenic to mammalian cells, as well as the possibility that it may cause DNA damage in the host, have all been raised as potential concerns.